Merancang Strategi Branding Toko Oleh-Oleh Telur Asin Moel Suti Dengan Persepsi Strategi Harga, Produk Dan Kepuasan - Wiyanti, Sari; Feldi Aji Purnama,; Muhammad Rizki Mubarok, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Competition in the salted egg industry in Brebes Regency is increasing along with the increasing number of producers with various innovations in flavors, packaging, and marketing strategies. This condition requires local business actors, including Moel Suti salted eggs, to design effective branding strategies to maintain market share and consumer loyalty. This study aims to analyze the influence of pricing strategies and product quality on customer satisfaction and to design an appropriate branding strategy for Moel Suti Brebes salted eggs. This study uses a descriptive quantitative approach with data collection techniques through distributing questionnaires to 100 respondents selected using accidental sampling. The variables in this study include Pricing Strategy (X1), Product Quality (X2), Customer Satisfaction (Y1), and Branding Strategy (Y2). Data analysis was carried out using validity and reliability tests, multiple linear regression, T-test, F-test, and coefficient of determination. The results of the study indicate that pricing strategies and product quality have a positive effect on customer satisfaction, and customer satisfaction has a significant effect on branding strategies. These findings indicate that the branding success of Moel Suti salted eggs is strongly influenced by consumer perceptions of value and experience. Based on these results, an integrated branding strategy based on improving product quality, setting competitive prices, and strengthening brand image through packaging and digital promotions is needed to strengthen the business's position in the regional souvenir market